Study and Analysis of Unmanned Solar Powered Vehicles Thite: Exploring the Potential of Unmanned Solar Powered Vehicles in Earth Observation and Telecommunication Systems (Journal of Advances and Scholarly Researches in Allied Education, 2011)
Stratosphericplatforms, geostationary located at altitudes  of   17 – 25 km, offer the  possibility of becoming   a  new    generation   of  infrastructural elements for future Earth  observation and  telecommunication   systems. They can act as pseudo- satellites, but   with   the  advantage  of  being  much cheaper and  closer  to the ground and  they  can per- form   missions  that  offer   greater  flexibility.  They could be self-launched, easily recovered for maintenance, whenevernecessary, and moved to cover different regions,  if  desired.  They   allow   a more detailed land  vision, due totheir  relative closeness to the  Earth, at  a much lower  cost than conventional satellites; furthermore they are geostationary locatedand  do not suffer from typical  satellite revisiting time limits  from 12 h up to 20 days. These  platforms could cover  a wide range of applications: real-time monitoring of seismic-risks or volcanicareas,  early  forest fire detection, border securitysurveillance, pipeline, and  power-linesurveys;  telecommunication servicessuch  as cellular-telephone networks,photogram- metry,  hydrographicmonitoring system, agriculture monitoring, etc.